PENGARUH KESEMPATAN INVESTASI DAN KEBIJAKAN HUTANG TERHADAP KEBIJAKAN DIVIDEN - purnamasari, imas; waspada, Ikaputera; mayasari, mayasari (Program Studi Akuntansi FPEB UPI, 2019)
AbstractThe purpose of the research is to find investment opportunities and debt policy affect Â of dividend policy. The object of research is companies in the basic and chemical industry sectors during the period 2006-2015. The company which became the study population was 64 companies. The sampling technique used in this study was purposive sampling method, based on the results of sampling in 10 companies for 10 years so that 100 observation data were obtained. The data used in the study is secondary data in the form of panel data. The method used in this research is descriptive verification method. Statistical analysis used in this research is multiple linear regression panel data analysis with regression significance test (Test F) and significance test of regression coefficient (t test). The results of the F Test statistic indicate that the regression model can be used to draw conclusions. The results of t-test statistics show that investment opportunities have a significant positive effect on dividend policy, and debt policy has a significant negative effect on dividend policy.